Keanekaragaman Jenis dan Struktur Vegetasi Herba di Taman Wisata Alam Iboih, Sabang - Hidayat, Muslich; Anistia (KENANGA : Journal of Biological Sciences and Applied Biology, 2026)
Terrestrial ecosystems, particularly tropical forests, possess the highest biodiversity and play a crucial role in global environmental balance. Herbaceous vegetation, as a key component of forest ecosystems, serves as ground cover, maintains soil moisture, supports nutrient cycling, reduces erosion, and provides habitat for small organisms. This study aims to analyze the species composition, dominance levels, and diversity of herbaceous vegetation in the Iboih Nature Tourism Park (TWA) area, Sabang. The research was conducted in May 2024 using vegetation analysis methods with parameters of density, frequency, and Importance Value Index (IVI). The results recorded 41 herbaceous plant species from various families. The species with the highest IVI was Asplenium nidus (bird’s nest fern) at 16.826, followed by Pteris ensiformis (14.083). The Shannon-Wiener diversity index (H’) value was 3.48, which is classified as high, indicating a stable, productive community that is not excessively dominated by any particular species. Environmental factors such as average soil moisture of 81%, air humidity of 78%, pH of 6.7, and temperature of 30.3°C support optimal growth of herbaceous vegetation. This study is expected to serve as a basis for the sustainable management of the Iboih Nature Tourism Park (TWA). Keywords: Vegetation; herbs; forest, Nature Tourism Park